1998
DOI: 10.1007/s11626-998-0079-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a human fibroblast cell line producing tumor necrosis factor α (KMST-6/TNF) and growth inhibitory effects of its conditioned medium on malignant cells in culture

Abstract: To develop a new gene therapy model for cancer, a clonal cell line (KMST-6/TNF) which produces human tumor necrosis factor alpha (hTNF-alpha) has been developed by introducing hTNF-alpha cDNA into a human immortal fibroblast cell line (KMST-6). The conditioned medium (CM) of KMST-6/TNF cells inhibited the growth of various malignant human cell lines, but not that of normal human fibroblasts. Although the growth inhibitory effects of KMST-6/TNF CM were neutralized to a considerable degree by anti-TNF-alpha anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…These and other findings indicate the potential for using TNF gene-transduced tumor cells as a vaccine [113]. Others transfected fibroblasts with the TNF gene and showed that these cells started to produce TNF and had antitumor activities [114]. Intratumoral injection of the TNF gene in a suitable vector and concomitant irradiation resulted in a complete tumor regression in over 70% of xenografted malignant human gliomas in athymic nude mice [115].…”
Section: The Promisesmentioning
confidence: 96%
“…These and other findings indicate the potential for using TNF gene-transduced tumor cells as a vaccine [113]. Others transfected fibroblasts with the TNF gene and showed that these cells started to produce TNF and had antitumor activities [114]. Intratumoral injection of the TNF gene in a suitable vector and concomitant irradiation resulted in a complete tumor regression in over 70% of xenografted malignant human gliomas in athymic nude mice [115].…”
Section: The Promisesmentioning
confidence: 96%